Development of Nomograms to Predict the Recovery of Erectile Function Following Radical Prostatectomy. Issue 11 (11th September 2019) - Mulhall, John P.; Kattan, Michael W.; Bennett, Nelson E.; Stasi, Jason; Nascimento, Bruno; Eastham, James; Guillonneau, Bertrand; Scardino, Peter T.
Abstract: Introduction: Given the number of confounders in predicting erectile function recovery after radical prostatectomy (RP), a nomogram predicting the chance to be functional after RP would be useful to patients' and clinicians' discussions. Aim: To develop preoperative and postoperative nomograms to aid in the prediction of erectile function recovery after RP. Main Outcome Measures: International Index of Erectile Function (IIEF) erectile function domain score-based erectile function. Methods: A prospective quality-of-life database was used to develop a series of nomograms using multivariable ordinal logistic regression models. Standard preoperative and postoperative factors were included. Main Outcome Measures: The nomograms predicted the probability of recovering functional erections (erectile function domain scores ≥24) and severe erectile dysfunction (≤10) 2 years after RP. Results: 3 nomograms have been developed, including a preoperative, an early postoperative, and a 12-month postoperative version. The concordance indexes for all 3 exceeded 0.78, and the calibration was good. Clinical Implications: These nomograms may aid clinicians in discussing erectile function recovery with patients undergoing RP. Strengths & Limitations: Strengths of this study included a large population, validated instrument, nerve-sparing grading, and nomograms that are well calibrated with excellent discrimination ability. Limitations include current absence of external validation and an overall low comorbidity index. Conclusions: It is hoped that these nomograms will allow for a more accurate discussion between patients and clinicians regarding erectile function recovery after RP.